DISCURSIVE ARTICULATION OF HOSTILITY AND VULNERABILITY EMOTIONS IN CUSTOMER-COMPANY INTERACTION - Maria das Graças de Santana Salgado (Gragoatá, 2004)
This work investigates the discourse of emotion in business interaction through the analysis of letters from clients addressed to insurance company, observing the relationship between the client's perception of the rights and duties of participants and the expression of emotions toward the company. To this purpose, the study uses the framework derived from politeness theory and from the anthropology of emotions taking into consideration face honoring or face threatening emotions. Given that emotion is a cultural artifact and a discursive practice, this investigation has observed that the break of the rights of client triggers the expression of hostility and vulnerability emotion and reveals relevant aspects of Brazilian culture in the interaction analysed.